Study on the evolution characteristics and influencing factors of frost heave on kaolin clay during the horizontal freezing process - Yue Liu; Yupeng Shen; Peng Jing (Scientific Reports)
Abstract Horizontal frost damage is a significant hazard threatening the safety of structures in cold regions. The frozen fringe represents the transitional zone between unfrozen and frozen soil. Its formation and migration not only directly influence the distribution of water during freezing but also play a significant role in the frost heave behavior. This study employed self-developed horizontal frost heave equipment to conduct seven experiments, exploring the effects of initial water content and dry density on the development of the frozen fringe in kaolin clay. As the initial water content increases, the water migration speed accelerates, and frost heave increases. The experimental results show that for every 5% increase in initial water content, the frost heave increases by an average of 3.43 mm. With increasing initial dry density, frost heave decreases, and the water migration speed decreases. For every 0.1 g/cm3 increase in initial dry density, the frost heave increases by an average of 3.26 mm. The study also found that the frozen fringe does not strictly advance in the vertical direction, which may have a potential impact on the structural integrity. Based on these experimental results, this study proposes an improved method for predicting the frozen fringe using the freezing point, building upon the Mizoguchi model, and validates its accuracy with field data. The research provides a theoretical basis for the design of slopes, retaining walls, and foundation pits, as well as for the implementation of frost heave prevention measures in cold regions.